Iniciação ao estudo da dinâmica de rotação de um satélite em variáves de Andoyer - Braz, Gabriella Aureliano [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The dynamics of the rotation of a satellite is an old and classical problem, specially in the Euler formalism. However, with these variables, even in torque free motion problem, the integrability of the system is far from trivial, mainly when the three moments of the inertia are not equal. Another disadvantage occurs when the inclinations between some plans are null or close to zero, so the nodes become undetermined. In this work, we propose the use of modern Andoyer's variables. These are a set of canonical variables and therefore some significant advantages can be obtained when dealing with perturbation methods. On other the hand, the integrability of the torque free motion becomes very clear, as the system is reduced to a problem of one degree of freedom. The elimination of the singularities mentioned above, can be solved very easily, with Pincaré-type variables. In this work we give the background concepts of the Andoyer's variables and the disturbing potential is obtained for the rotational dynamics of a satellite perturbed by a planet. In the case when A = B (moments of inertia) and due to the current variables, the averaged system is trivially obtained through very simple integrations

A dinâmica de rotação de um satélite é um velho clássico problema da mecânica, principalmente em variáveis de Euler. No entanto, nestas variáveis, mesmo no caso de ausência total de torques, a integrabilidade do problema de rotação não é óbvia, principalmente quando os três momentos de inércia são desiguais. Há ainda uma outra desvantagem das variáveis de Euler, quando algumas inclinacões são nulas ou próximas de zero, ocasião em que os nodos ficam indeterminados. Neste trabalho, propomos o uso das modernas variáveis de Andoyer. Estas formam um conjunto canônico e por isso oferecem significativas vantagens em métodos de perturbações. Por outro lado, a integrabilidade do problema livre de torques fica óbvia, assim como o sistema é reduzido a um problema de um grau de liberdade. A eliminação das singularidades mencionadas acima, podem ser resolvidas facilmente com mais uma transformação canônica (canônicas polares de Poincaré). Então neste trabalho, introduzimos as variáveis de Andoyer e montamos o potencial perturbador para o caso de um satélite perturbado por um planeta. No caso onde A = B e pelo fato das coordenadas serem canônicas, a obtenção do sistema médio é bastante trivial, através de simples integrações
Keywords: Astronomia; Perturbação (Astronomia); Satélites artificiais - Rotação; Fisica